The fermented non-digestible fraction of spent coffee grounds induces apoptosis in human colon cancer cells (SW480) (2017)
ABSTRACT: Gut flora-mediated non-digestible/unabsorbed fraction of spent coffee grounds (hgf-NDSCG) was evaluated for its chemopreventive effect and molecular mechanisms involved on human colon adenocar- cinoma SW480 cell survival. Small intestinal digestion released bioavailable ascorbic, chlorogenic and gallic acids from hgf-NDSCG reducing oxidative stress. The hgf-NDSCG inhibited SW480 growth (LC50-19%) dose dependently by decreasing glutathione/oxidized glutathione (GSH/GSSG) ratio, indicat- ing a cellular oxidative stress process. Flow cytometry analysis demonstrated the presence of apoptotic cells in a hypodiploid sub G0/G1-peak as a consequence of partial DNA loss. The pro-apoptotic mechanism of hgf-NDSCG was confirmed by SW480 cell toxicity induced by increased Caspase-3 activity and mitochondria dysfunction modulating oxidative stress using Annexin V and DiOC2(3) staining assays. The chemopreventive effects of spent coffee grounds (SCG) indicate that polyphenols present in hgf-NDSCG, digested and fermented by colon microbiota, can inhibit survival of human colon cancer cell and offer effective prophylactic value to prevent colon cancer.